Immunogenetics of fungal diseases - Carvalho, Agostinho (Springer, 2017)
This book provides up-to-date information on immunogenetics of fungal diseases in the context of primary and acquired immunodeficiencies. Different aspects of this emerging field are covered, including epidemiology of fungal diseases, innate and adaptive antifungal immunity, and the role of immunogenetics in defining susceptibility to fungal diseases in primary (CMC, CGD, etc.) immunodeficiencies and hematologic patients. The available information will also be discussed in the scope of new biomarker discovery and development of immunotherapeutic approaches for personalized diagnostics and therapy. The book addresses Professors, researchers and advanced students of Medicine, Immunology, Microbiology and Genetics.
Keywords: Mycoses -- Immunological aspects.; Mycoses -- Genetic aspects.; Immunogenetics.; elektronické knihy; electronic books